Controle postural pré e pós intervenção presencial ou domiciliar em pacientes com osteoartrose de joelho: um ensaio clínico randomizado - Vaz, Évelin Santos (2022)
Knee osteoarthritis (OA) is a chronic, degenerative, multifactorial and progressive disease that causes several musculoskeletal changes such as reduced strength, decreased range of motion and flexibility, higher levels of pain and decreased proprioception and postural control. . Postural control provides stability and conditions for individuals to assume and maintain the desired body position, being reduced along with the general functional capacity in patients with OA. To reduce these changes, one of the intervention strategies is physical exercise. The objective of this dissertation was to evaluate the postural control of patients with knee OA pre and post protocol of exercises applied in person or with home guidance. The study included 48 individuals of both sexes, aged between 40 and 65 years and with a clinical diagnosis of knee OA. Patients were evaluated for functional capacity (Western Ontario and McMaster Universities Osteoarthritis Index questionnaire, WOMAC), gait speed (40-meter walk test) and postural control (strength platform, AMTI, model OR6-6-2000). Postural control was evaluated under eyes open and eyes closed, with and without the use of a foam surface (Airex balance pad), in three 30-second attempts, with a 1-minute rest interval between them. The acquisition frequency was 100 Hz and the data were filtered by a fourth-order Butterworth digital filter with a cutoff frequency of 10 Hz, and processed through a Matlab routine. After the evaluations, participants were randomized into two groups: group of face-to-face group exercises (EGG) (n=23, 56.22±7.51 years, 85.60±17.86 kg, 1.59±0.09 m and BMI 33.61±5.94 kg/m²) and home exercise group (GED) (n=25, 57.76±5.46 years, 85.30±15.43 kg, 1.61±0.08 m and BMI 33.30±7.28 kg/m²). Both groups followed the same 6-week exercise protocol. The GEG carried out two in-person exercise sessions per week, in groups of 4 to 5 subjects, and the GED carried out a weekly in-person and individual exercise session and another at home. The results showed that the groups showed improvement in the WOMAC domains, pain (p<0.001), stiffness (p<0.001), function (p<0.001), total (p<0.001) after treatment, and there were no differences between the groups for pain (p=0.85), stiffness (p=0.72), function (p=0.84) and total score (p=0.89). Both groups improved their walking speed (p<0.001) after treatment, regardless of the allocated group. Regarding postural control, there were no statistically significant differences in the variables of displacement of the center of pressure (anteroposterior and mediolateral) before and after intervention with exercises, regardless of the group. Regarding the variable speed of the center of pressure, the patients increased the speed of oscillation of the center of pressure before and after treatment in the condition of eyes closed. Postural control after the intervention. Patients showed an increase in walking speed and in all WOMAC domains, regardless of the group that performed the activities.